Penggunaan Tindak Tutur Lokusi, Ilokusi, dan Perlokusi pada Postingan Facebook Grup Warga Media Sosial Rengaspendawa pada Kajian Pragmatik - Siti Mutmainah; Ghufroni Ghufroni; Nurchalistiani Budiana (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe (1) how the use of locutionary speech acts in the Rengaspendawa social media community group facebook posts in pragmatic studies, (2) how the use of illocutionary speech acts in the Rengaspendawa social media citizen group facebook posts in pragmatic studies, (3) how to use perlocutionary speech acts in the Facebook post of the Rengaspendawa citizen group on a pragmatic study. The method in this study used a qualitative descriptive method. Data collection techniques using observation techniques, reading techniques, note-taking techniques, and documentation techniques. The data analysis technique uses pragmatic studies, and research procedures that produce descriptive data in the form of written words. Data analysis was carried out by describing the data on the use of illocutionary and perlocutionary speech acts on the Facebook posts of the Rengaspendawa social media citizen group in pragmatic studies, which were obtained from the scrinshoot of the Rengaspendawa social media community group facebook post, then identified, and clarified according to the data in the post. This study aims to describe (1) how the use of locutionary speech acts in the Rengaspendawa social media community group facebook posts in pragmatic studies, (2) how the use of illocutionary speech acts in the Rengaspendawa social media citizen group facebook posts in pragmatic studies, (3) how to use perlocutionary speech acts in the Facebook post of the Rengaspendawa citizen group on a pragmatic study. The method in this study used a qualitative descriptive method. Data collection techniques using observation techniques, reading techniques, note-taking techniques, and documentation techniques. The data analysis technique uses pragmatic studies, and research procedures that produce descriptive data in the form of written words. Data analysis was carried out by describing the data on the use of illocutionary and perlocutionary speech acts on the Facebook posts of the Rengaspendawa social media citizen group in pragmatic studies, which were obtained from the scrinshoot of the Rengaspendawa social media community group facebook post, then identified, and clarified according to the data in the post.